2020
DOI: 10.1021/jacs.9b11598
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Complexity in Fuel-Driven DNA Nanostructures with Autonomous Reconfiguration of Multiple Dynamic Steady States

Abstract: We introduce pathway complexity on a multicomponent systems level in chemically fueled transient DNA polymerization systems, achieving autonomous evolution over multiple structural dynamic steady states from monomers to dimers, oligomers of dimers to randomized polymer structures before being ultimately degraded back to monomers once the fuel is consumed. The enabling key principle is to design monomer species having kinetically selected molecular recognition in the structure-forming step and which are reconfi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…ATP-fueled systems for autonomous systems design relate to the emerging and very active field of non-equilibrium self-assemblies. [42,81,84,88,200] Even though an elaboration on all differences of the various approaches is not the central part of this review, it is important to point to some major ones. By discriminating how ATP is stored and used in the assembled structures, two major types of ATP fuel-driven self-assemblies have been developed.…”
Section: Summary Perspective and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…ATP-fueled systems for autonomous systems design relate to the emerging and very active field of non-equilibrium self-assemblies. [42,81,84,88,200] Even though an elaboration on all differences of the various approaches is not the central part of this review, it is important to point to some major ones. By discriminating how ATP is stored and used in the assembled structures, two major types of ATP fuel-driven self-assemblies have been developed.…”
Section: Summary Perspective and Outlookmentioning
confidence: 99%
“…Compared to the standard 4 nt sticky end, 1 nt sticky ends showed a significant lag time for the ATP‐fueled DNA polymerization due to their much weaker ability for hybridization. [ 200 ] This difference allowed to introduce pathway complexity in a multicomponent systems by designing monomer species having kinetically selected molecular recognition in the structure‐forming step. This could be realized for instance by combining two complementary AB/AʹBʹ monomer species (M3, M4) bearing a 1 nt and a 4 nt sticky overhang on each side ( Figure ).…”
Section: Atp‐fueled Self‐assembling Systems With Autonomous Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, in all these cases adaptability originates from changes in the free energy landscape caused by the external trigger. The transient self‐assembly of DNA‐based nanostructures and the kinetic control of DNA‐based nanodevices has only recently been achieved using synthetic gene circuits or DNA‐recognizing enzymes as the fuel‐consuming units . DNA self‐assembly in these systems is characterized by the instalment of a dynamic kinetic steady state in which an anabolic reaction leads to DNA‐hybridization, whilst a catabolic enzymatic reaction concurrently causes disassembly by hydrolysing hybridized DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, for simple, single-species ERNs of this type, we confirmed that i) the degree of ligation in the dynamic steady state (DySS) plateau depends on the ratio of ligase/REase, ii) structural dynamics (constant bond shuffling and subunit exchange) occurs, and iii) the lifetimes depend on the ATP concentration. [16,18,19] The adaptive transformation will operate as follows ( Figure 1 b): First, ligase (black) and ATP polymerize the three monomers into a mixed copolymer, serving as a homogenous initial material state. Afterwards, we add two REases (green, red) as signals with a certain ratio to dynamize the system.…”
mentioning
confidence: 99%